PENERAPAN MODEL PEMBELAJARAN PENJAS INOVATIF (IU-07-1) MENGGUNAKAN METODE PROGRESS CARDS DALAM PEMBELAJARAN PENJAS MATERI MELEMPAR KE SASARAN (STUDI PADA SISWA KELAS 2 SDN KARANGJATI I DAN SDN CUKURGULING 3, KECAMATAN LUMBANG, KABUPATEN PASURUAN, TAHUN PELAJARAN 2011/2012) - SURAHMAN, AFFAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The aim of this research is to know the improve of result of the study, interest, motivation, cooperation, and also improve the quality of teacher and student during learning process between experiment class and control class after they held the innovation learning of physical education using progress cards method in target throwing material. The population which is used in this research is the student of grades II in elementary public school of Karangjati I as experiment class, consists of 29 students and the student in elementary public school of Cukurguling 3 as control class, consists of 21 students. The technique of data population which is used in this research is using result of study scoresheet, FCE quetionniare, observation class, and target throwing test.    Based on the result of the data analysis of this research, it can be concluded that there is different in result of target throwing study between experiment class and control class after using progress cards method on innovation learning model of physical education (IU-07-1). This can be finded from different of procent increase at the result of pretest and posttest target throwing. Procently, the result of procent increase of target throwing for experiment class 28.57 % in amount. While, on control class 0.00 % in amount. Keywords: learning model, innovation of physical education (IU-07-1), learning method, progress cards, study result, target throwing.